Eyes on the Mind: Investigating the Influence of Gaze Dynamics on the Perception of Others in Real-Time Social Interaction - Pfeiffer, Ulrich; Schilbach, Leonhard; Timmermans, Bert; Jording, Mathis; Bente, Gary; Vogeley, Kai (Frontiers in Psychology, 2012)
Social gaze provides a window into the interests and intentions of others and allows us to actively point out our own. It enables us to engage in triadic interactions involving human actors and physical objects and to build an indispensable basis for coordinated action and collaborative efforts. The object-related aspect of gaze in combination with the fact that any motor act of looking encompasses both input and output of the minds involved makes this non-verbal cue system particularly interesting for research in embodied social cognition. Social gaze comprises several core components, such as gaze-following or gaze-aversion. Gaze-following can result in situations of either ‘joint attention’ or ‘shared attention’. The former describes situations in which the gaze-follower is aware of sharing a joint visual focus with the gazer. The latter refers to a situation in which gazer and gaze-follower focus on the same object and both are aware of their reciprocal awareness of this joint focus. Here, a novel interactive eye-tracking paradigm suited for studying triadic interactions was used to explore two aspects of social gaze. Experiments 1a and 1b assessed how the latency of another person’s gaze reactions (i.e. gaze-following or gaze-aversion) affected participants’ sense of agency, which was measured by their experience of relatedness of these reactions. Results demonstrate that both timing and congruency of a gaze reaction as well as the other’s action options influence the sense of agency. Experiment 2 explored differences in gaze dynamics when participants were asked to establish either joint or shared attention. Findings indicate that establishing shared attention takes longer and requires a larger number of gaze shifts as compared to joint attention, which more closely seems to resemble simple visual detection. Taken together, novel insights into the sense of agency and the awareness of others in gaze-based interaction are provided.